Presence and distribution of leptin and its receptor in the gut of adult zebrafish in response to feeding and fasting. (11th July 2018) - Garcia‐Suarez, Olivia; Cabo, Roberto; Abbate, Francesco; Randazzo, Basilio; Laurà, Rosaria; Piccione, Giuseppe; Germanà, Antonino; Levanti, Maria
Abstract: Leptin is an anorectic hormone secreted mainly by peripheral adipocytes but also by other central and peripheral tissues. It acts by means of a receptor called OB‐R, influencing not only appetite and body mass but being also involved in many fields like endocrinology, metabolism and reproduction. Immunohistochemistry and qRT‐PCR techniques were, respectively, used to demonstrate the presence of leptin and its receptor in the gut of adult zebrafish and to evaluate the leptin gene expression response to feeding and fasting. Immunoreactivity for the antibodies utilized was demonstrated in feeding but not in fasting fish, and the gene expression analysis corroborates the data obtained by immunohistochemistry. Therefore, all the obtained results support the hypothesis of the role of this hormone in food regulation in zebrafish.